Causal Relationship Model of Student Loyalty in Thai Private Higher Education Institutions - ตระกูลเกษมสุข ประภาวรรณ; สินจินดาวงศ์ สิรินธร; มณีศรี ชารี (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2018)
Abstract This research aims to develop and validate a causal relationship model of student loyalty to Thai private higher education institutions. The questionnaire was distributed and completed by 557 students in five Thai private higher education institutions. The result of a causal relationship model shows that service quality, student satisfaction and university image are factors influencing student loyalty to Thai private higher education institutions. This result conforms to the research framework and thus has construct validity. Student satisfaction is the most important factor for student loyalty, then university image and service quality is the only factor which has minus direct effect on student loyalty. Meanwhile, service quality shows high direct effect on student satisfaction in contrast to the minus direct effect on university image. The result also shows that student satisfaction and university image have a reciprocal relationship. While student satisfaction notes high direct effect on university image, university image has no direct effecton student satisfaction.